The effects of dietary lysine level on performance of pigs weaned at two weeks of age - R C Thaler; Robert D Goodband; Robert H Hines; Jim L Nelssen (Kansas Agricultural Experiment Station Research Reports, 1988)
One-hundred fifty pigs weaned at 14 ± 2 days of age and averaging 9.8 ± 2.8 lb were used to determine the effects of increasing levels of dietary lysine on pig performance. Pigs were fed a pelleted corn-soybean meal diet (1.10% lysine) containing 20% dried skim milk and 14.4 % lactose or diets containing 1.25, 1.40, 1.55, or 1.70% lysine provided by L-lysine HCI. Average daily gain (ADG), feed conversion (F/G), and plasma urea concentrations were determined on day 7, 14, and 21 of the experiment. On day 7, ADG increased linearly (P<.05) with increasing lysine level. By day 21, ADG was increased 12% (linear and quadratic P<.15) for those pigs fed the 1.40% lysine diet. On day 7, 14, and 21, F/G improved (linear and quadratic P<.02) and plasma urea concentrations decreased (linear, quadratic, and cubic P<.O 1) as lysine level increased. Feed intake was not affected by dietary treatment (P>.20). At the end of the 21 day experimental period, all pigs were switched to a corn-soybean meal diet (1.25% lysine) containing 15% dried whey for an additional 21 days to determine any compensatory performance from previous lysine treatment. During this period (22 to 42 days), there were no differences in pig performance. For the overall experiment (0 to 42 days), ADG was increased 5% (P>.30) and F/G improved 6% (linear P<.l1; quadratic P<.0 1) as lysine level was increased during the first 3 wk postweaning. Our results indicate that growth performance of early weaned pigs (<10 lb) was optimized by a diet containing at least 1.40% lysine for the first 3 wk postweaning.; Swine Day, Manhattan, KS, November 17, 1988
Keywords: Swine day; 1988; Kansas Agricultural Experiment Station contribution; no. 88-149-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 556; Swine; Lysine requirement; Growth; Two-week old pigs; Compensatory gain